E-management a scuola: un quadro delle questioni - Pier Cesare Rivoltella (LED Edizioni Universitarie, 2014)
E-management and School: Key Issues This article aim is to provide reflection and suggestions about the relationship between digital technologies and School Management. Doing this its main focus is about what school managers have to take care of, that is: funding, sharing, research and teachers' training. New technologies help school principals to imagine a new relationship with market: this means to imagine new funding activities, from sponsoring to crowd-sourcing. Sharing is provided by the internet and wi-fi development: working together is the way the schools have to choose for being more effective in taking note of what stakeholders have to ask them. Finally, e-management is about research and teachers' training: in this case digital technologies are good tools and environments for fostering organizational learning and human resources development. The second part of the article highlights risks and difficulties for helping managers in a more concrete way.